How college students cope during the pandemic: A qualitative analysis of mental health module outputs - Ines, Jennifer V. (Animo Repository, 2023)
The first few years of the COVID-19 pandemic have been tough for most people, especially students. College students experiencing high-stress levels while learning remotely have been reported. Students’ social development has also been affected as they missed out on experiencing University life. Such unfortunate circumstances can genuinely impact one’s mental health and development. People cope differently with every challenge. Effective coping strategies can protect one’s mental health. The qualitative phenomenological study aimed to shed light on the types of coping strategies that college students utilized and discuss the things they felt grateful for during the early part of the COVID-19 pandemic. Using the content analysis method, module outputs of students from an online mental health course were examined. Data were sourced from photo collages and essays of students providing answers to the questions: “What coping strategies do you use to cope with the pandemic?” and “What are you grateful for during the pandemic?”. Twenty Filipino male and female participants were randomly selected from a total of 81 Business students coming from two (2) sections that took the online course. Findings revealed that students employed various cognitive and behavioral coping strategies during the pandemic. These included maintaining social connections, engaging in leisure or recreational activities, taking care of one’s physical body, using self-management techniques, engaging in religious activities, engaging in relaxation activities, and self-reflection. Findings also showed how students remained hopeful amidst the global health crisis by being grateful for their social support, being able to maintain good health and safety, having access to basic needs, enjoying certain privileges, being grateful to God, having an opportunity for self-reflection and being inspired by certain community members during the pandemic.